Pink smog becoming Weetzie Bat - Francesca Lia Block (New York : HarperTeen, 2012)
When Weetzie Bat is a thirteen-year-old junior high school outcast mourning the life her family lost when their cottage in the Los Angeles hills burned down, her father leaves her alcoholic mother without telling either of them where he is going and Weetzie learns how to stand up for herself and to find beauty in even the most difficult situations.